2022
DOI: 10.1037/dev0001335
|View full text |Cite
|
Sign up to set email alerts
|

When does 1 + 1 not equal 2? The relative advantage of public school-based pre-k versus Head Start for low-income children’s kindergarten cognitive and self-regulatory skills.

Abstract: Decades of research suggest that both Head Start and public pre-kindergarten (pre-k) programs boost low-income preschoolers’ kindergarten skills. What is not yet well understood is whether there are relative advantages of transitioning from Head Start after 1 year into a school-based public pre-k program for the year immediately before kindergarten for children’s developing cognitive and self-regulation skills. This is an important question, because in many communities Head Start and school-based pre-k program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Recent consensus statements from experts have concluded that public preschool attendance has an immediate positive effect on children's early language, literacy, and math skills—effects detected most often at the end of the preschool year or at the start of kindergarten (Phillips et al, 2017; Yoshikawa et al, 2013). These statements are based on studies of scaled‐up contemporary public preschool programs in Boston, Tulsa, Tennessee, New Mexico, Georgia, and North Carolina (e.g., Gormley et al, 2008; Henry et al, 2006; Hustedt et al, 2021; Jenkins et al, 2016; Johnson et al, 2022; Lipsey et al, 2018; Peisner‐Feinberg & Schaaf, 2011; Weiland & Yoshikawa, 2013), as well as several multi‐state pre‐k studies (Barnett et al, 2018; Wong et al, 2008) and the national Head Start Impact Study (HSIS; Puma et al, 2012).…”
Section: Prior Research Estimating Preschool Benefitsmentioning
confidence: 99%
“…Recent consensus statements from experts have concluded that public preschool attendance has an immediate positive effect on children's early language, literacy, and math skills—effects detected most often at the end of the preschool year or at the start of kindergarten (Phillips et al, 2017; Yoshikawa et al, 2013). These statements are based on studies of scaled‐up contemporary public preschool programs in Boston, Tulsa, Tennessee, New Mexico, Georgia, and North Carolina (e.g., Gormley et al, 2008; Henry et al, 2006; Hustedt et al, 2021; Jenkins et al, 2016; Johnson et al, 2022; Lipsey et al, 2018; Peisner‐Feinberg & Schaaf, 2011; Weiland & Yoshikawa, 2013), as well as several multi‐state pre‐k studies (Barnett et al, 2018; Wong et al, 2008) and the national Head Start Impact Study (HSIS; Puma et al, 2012).…”
Section: Prior Research Estimating Preschool Benefitsmentioning
confidence: 99%